Piezoelectric Actuators : Vector Control Method: Basic, Modeling and Mechatronic Design of Ultrasonic Devices - Giraud, Frédéric; Giraud-Audine, Christophe (Butterworth-Heinemann, 2019)
Piezoelectric Actuators: Vector Control Method: Base, Modeling and Mechatronic Design of Ultrasonic Devices guides researchers and engineers through the process of implementing the vector control method (VCM) in their systems. The book presents which measurements can be made, how to visualize a variable as a rotating vector, about the angular position of the rotating reference frame, how to calculate the parameters of the controllers, and how to observe key variables. Additionally, the book focuses on the modeling of PE ultrasonic transducers and investigates the energy conversion process in an ultrasonic transducer.